The clinical characteristics and treatment response of patients with chronic obstructive pulmonary disease with low body mass index - Song, Qing; Zhou, Aiyuan; Lin, Ling; Li, Xueshan; Cheng, Wei; Liu, Cong; Peng, Yating; Zeng, Yuqin; Yi, Rong; Liu, Yi; Li, Xin; Chen, Yan; et al. (Frontiers in Pharmacology, 2023)
Background: This study aimed to analyze the clinical characteristics and treatment response of patients with chronic obstructive pulmonary disease (COPD) with low body mass index (BMI). Methods: In this cross-sectional study, we enrolled patients with stable COPD from database setup by the Second Xiangya Hospital of Central South University. We classified the patients into three groups based on BMI: low BMI (<18.5 kg/m2), normal BMI (≥18.5 and <24.0 kg/m2), and high BMI (≥24 kg/m2) groups. We defined clinically important deterioration (CID) as a COPD Assessment Test (CAT) score increase of ≥ 2 and minimum clinically important difference (MCID) as a CAT score decrease of ≥ 2 during six months of follow-up. We recorded the number of exacerbations and mortality during one year of follow-up. Results: A total of 910 COPD patients were included and 144 (15.8%) patients in low BMI, 475 (52.2%) in normal BMI and 291 (32.0%) in high BMI groups. Patients with low BMI had worse pulmonary function, higher symptom scores and exacerbations in the past year compared with normal and high BMI groups (P < 0.05). Logistic regression analysis revealed that age, Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades 3 and 4, and hospitalizations in the past year were independent risk factors for patients with low BMI (P < 0.05). After one year of follow-up, patients with low BMI had higher mortality and number of hospitalizations. Patients with low BMI were more likely to attain CID and less likely to attain MCID compared with patients with high BMI (P < 0.05). In addition, patients with low BMI treated with long-acting β2-agonist (LABA)+long-acting muscarinic antagonist (LAMA) and LABA+LAMA+inhaled corticosteroid (ICS) were more likely to attain MCID than those treated with LABA+ICS and LAMA (P < 0.05). Conclusion: COPD patients with low BMI had worse pulmonary function, higher symptom scores, higher risk of future hospitalizations and mortality, and were less likely to attain MCID and more likely to attain CID. It is worth noting that patients with low BMI treated with LABA+LAMA and LABA+LAMA+ICS were more likely to attain MCID than those treated with LABA+ICS and LAMA.